The education and the social status of the nurse - Głowacka, Mariola; Mejsner, Marta; Humańska, Marzena (Nursing in the 21st Century, 2012)
THE EDUCATION AND THE SOCIAL STATUS OF THE NURSE The image of a nurse had diametrically changed over the centuries. From nuns through women of easy virtue to the nurses educated in the first Florence Nightingale’s nursing school. Today nursing is a dynamically developing scientific discipline basing on technical achievements, which derives from the humanities as well as from medical sciences. Aim. The aim of presented research was to determine professional status and social prestige of nurses in the assessment of the residents of Bydgoszcz district. The qualities that have been taken into account were knowledge, professional skills, education and social opinion about health services performed by nurses. The obtained results, i.e. knowledge of nurses’ prestige and the influencing factors allow finding a way to make this particular profession more attractive. Material and methods. The study was performed in the period from 10 September to 10 October 2011. Clinical diagnostic survey method was used with questionnaire of my own design. The study was conducted in a population declaring their place of residence in the district of Bydgoszcz. The study group comprised 100 persons. The recruitment of study participants was at random, arbitrary. Results. The majority of respondents was familiar with the issue of education of nurses and emphasized the need for training, mainly due to technological progress. A lot of the respondents who were hospitalized associated nursing profession with positive characteristics, and nurse’s commitment to work was rated high, but underestimated financially. Conclusions. Bachelor and/or master’s degree studies belonged to the group of positive factors which determined the social status of the nurse and in the opinion of respondents guaranteed the opportunity of work in the profession. Similar opinion concerned postgraduate education for nurses.